2021
DOI: 10.1001/jamaoncol.2021.4342
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Liver Biopsy in Diagnosis and Management of High-grade Immune Checkpoint Inhibitor Hepatitis in Patients With Cancer

Abstract: The utility of liver biopsy in diagnosis and management of immune checkpoint inhibitor (ICI) hepatitis is uncertain. [1][2][3] We examined the association of histology with management and outcomes of high-grade ICI hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…We acknowledge that other authors concluded in their series that, in ICI-related grade 3 liver injury, performing a liver biopsy was associated with a delay in starting CSs and did not result in a faster resolution of the hepatitis. 48 Importantly, in this report by Li et al, 12 of 107 biopsied patients (11%) did not actually have ICI hepatitis. In these cases, liver biopsy was therefore certainly of great help in avoiding potentially deleterious immunosuppressive therapy in an oncological context.…”
Section: Discussionmentioning
confidence: 62%
“…We acknowledge that other authors concluded in their series that, in ICI-related grade 3 liver injury, performing a liver biopsy was associated with a delay in starting CSs and did not result in a faster resolution of the hepatitis. 48 Importantly, in this report by Li et al, 12 of 107 biopsied patients (11%) did not actually have ICI hepatitis. In these cases, liver biopsy was therefore certainly of great help in avoiding potentially deleterious immunosuppressive therapy in an oncological context.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, we were limited by the absence of liver biopsies and incomplete serologic evaluations to diagnose alternative etiologies of liver injury. However, recent retrospective studies have indicated that liver biopsy does not necessarily influence the outcome or management of patients with grade 3 or 4 hepatotoxicity and that corticosteroids can be initiated in patients with moderate hepatocellular injury while other causes are being investigated ( 29 ). Furthermore, the histology of ILICI has been fairly heterogeneous to date so that liver biopsy may not necessarily impact clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 17 ] retrospectively analyzed a cohort of 213 patients who developed grade 3 or higher grade of hepatitis linked to ICIs therapy. The most common pattern of DILI was panlobular hepatitis.…”
Section: Role Of Liver Biopsymentioning
confidence: 99%
“…This study suggested that LB in patients treated with ICIs and developing grade 3 or higher liver injury presented a delay in the initiation of corticosteroid therapy and not associated with a faster resolution of liver inflammation. These authors also stated that LB can provide valuable information in patients who do not improve despite the indication of corticosteroids before another immunosuppressant is prescribed[ 17 ].…”
Section: Role Of Liver Biopsymentioning
confidence: 99%